2003
DOI: 10.1007/s00239-002-2431-0
|View full text |Cite
|
Sign up to set email alerts
|

The PRAT Purine Synthesis Gene Duplication in Drosophila melanogaster and Drosophila virilis Is Associated with a Retrotransposition Event and Diversification of Expression Patterns

Abstract: The Drosophila melanogaster Prat gene encodes amidophosphoribosyltransferase (PRAT; EC 2.4.2.14), which performs the first step in de novo purine nucleotide synthesis. Prat mutations have a recessive lethal phenotype that is found for other genes encoding enzymes in this pathway. The D. melanogaster genome project has revealed a second gene, CG10078 or Prat2, encoding a protein with 76% amino acid sequence identity with Prat. The two genes map to different arms of chromosome 3 and have different intron/exon or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This could explain the distinct spatial and temporal expression of Cyp307a1 and Cyp307a2 (Ono et al, 2006). In D. melanogaster, retrotransposition has generated two copies of amidophosphoribosyltransferase (Malmanche et al, 2003). These two paralogs are, like Cyp307a1 and Cyp307a2, expressed at different developmental stages.…”
Section: Gene Organization: the Cyp307 Family Of Orphansmentioning
confidence: 93%
“…This could explain the distinct spatial and temporal expression of Cyp307a1 and Cyp307a2 (Ono et al, 2006). In D. melanogaster, retrotransposition has generated two copies of amidophosphoribosyltransferase (Malmanche et al, 2003). These two paralogs are, like Cyp307a1 and Cyp307a2, expressed at different developmental stages.…”
Section: Gene Organization: the Cyp307 Family Of Orphansmentioning
confidence: 93%
“…Interestingly, there are a few genes that differentially respond to Wolbachia and virus, such as prat2. prat2 is a gene involved in the de novo synthesis of purine nucleotides (Ji and Clark, 2006;Malmanche et al, 2003), and one of the most strongly downregulated in the virus-responsive gene set, expressed at <0.01% of the level of expression in PBS-injected flies ( Figure 6B). While prat2 did not meet the threshold for statistical significance in the Wolbachia-responsive RNA-Seq analysis, prat2 was upregulated in Wolbachia-colonized flies 1.7-fold ( Figure 6B).…”
Section: Nucleotide Metabolism and Wolbachia Colonization Have Interamentioning
confidence: 99%
“…At the level of protein-coding function, retrotransposition has been identified as a minor but important mechanism for the creation of novel combinations of functional domains (Babushok et al 2007) and has also been identified as having the potential to create protein-coding loci de novo (Kaessmann et al 2009). However, while it has been estimated that more than 100 human protein-coding loci might have arisen by this route (Vinckenbosch et al 2006), very few retrotransposed loci have evidence of function at the protein level; notable exceptions include human GLUD2 (Shashidharan et al 1994) and Drosophila Prat (Malmanche et al 2003). While the increasing number of transcribed retrotransposed genes creates additional candidate protein-coding loci (Baertsch et al 2008), there is no evidence that proteins originate from such loci.…”
Section: Resurrected Pseudogenesmentioning
confidence: 99%